Emotional Intelligence and Social Networking Effects on Student Academic Achievement - Sengkey, Fenny; Flaviana Osin, Rosvita; Agus Anggayana, I Wayan (Akademi Komunitas MAPINDO, 2022)
This study aims to examine the influence of emotional intelligence and the impact of social media on student academic achievement in Akademi Komunitas Manajemen Perhotelan Indonesia. Data collection using a questionnaire. Determination of samples in this study using simple random techniques. This study took 50% of the total number of students. The results of the study show that emotional intelligence has a positive and significant effect on student achievement and the impact of social media has a positive and significant effect on student academic achievement in Akademi Komunitas Manajemen Perhotelan Indonesia. Affective domains such as interpersonal skills, stress management, adaptability, and general mode are slowly melding into learning instructional designs. Psychological characteristics are seen as necessary characteristics of successful students for the achievement of education programs. The use of social media also has a positive impact on students by being able to add the latest knowledge and information Keywords: emotional intelligence, social network, student academic achievement